2023
DOI: 10.3390/plants12020255
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Dependent Jasmonic Acid Effect on Pinus sylvestris L. Growth and Induced Systemic Resistance Indicators

Abstract: Due to temperature changes, forests are expected to encounter more stress than before, both in terms of biotic factors, such as increased insect attacks, and abiotic factors, such as more frequent droughts. Priming trees to respond to these changes faster and more effectively would be beneficial. Induced systemic resistance (ISR) is a mechanism that is turned on when plants encounter unfavorable conditions. Certain elicitors, such as jasmonic acid (JA) are known to induce plants’ metabolic response. However, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…can produce different amounts of phenols, flavonoids, and photosynthesis pigments [ 31 ]. Furthermore, we observed the same tendencies in ash, spruce, and pine trees as well as blueberries and lingonberries [ 32 , 43 , 47 , 53 , 54 ]. All these examples align perfectly with the findings of this study, whereby we observed statistically significant differences in the amounts of TPC, TFC and antioxidant scavenging capacity diverging in different half-sib families grown in the same site and belonging to the same population.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…can produce different amounts of phenols, flavonoids, and photosynthesis pigments [ 31 ]. Furthermore, we observed the same tendencies in ash, spruce, and pine trees as well as blueberries and lingonberries [ 32 , 43 , 47 , 53 , 54 ]. All these examples align perfectly with the findings of this study, whereby we observed statistically significant differences in the amounts of TPC, TFC and antioxidant scavenging capacity diverging in different half-sib families grown in the same site and belonging to the same population.…”
Section: Discussionsupporting
confidence: 67%
“…During this test, differences are determined by comparing the mean ranks of groups. A post hoc Dunn’s test was performed to indicate differences between individual pairs [ 32 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants can produce a large number of free amino acids and polyunsaturated fatty acids (PUFA) because the decomposition rate of proteins and lipids is greater than the synthesis rate in arid environments, and a large number of metabolites produced by the oxidation of PUFA are collectively called oxidized lipids (such as jasmonic acid, JA). Many of them are bioactive compounds that may directly participate in plant defense, communication with other organisms or signal transduction in plant development, defense responses and stress adaptation [22][23][24]. The substrate of lipoxygenase is a free polyunsaturated fatty acid (PUFA) with increased content under stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Induced systemic resistance (ISR) is a protective strategy of plants, through which plants can protect themselves from infections caused by pathogens, pests, etc. [26]. ISR can modify and enhance positive plant responses to stress by leveraging natural defenses, such as increased polyphenol levels, heightened antioxidant enzyme activity and improved photosynthetic pigments [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%